Generation of a Panel of Monoclonal Antibodies Against the Haemagglutinin-Neuraminidase Glycoprotein of Newcastle Disease Virus Strain Af2240 - Lee, Lin Kiat (2005)
The Malaysian velogenic-viscerotropic Newcastle disease virus (NDV) strain AF2240 is responsible for high mortality and morbidity. Monoclonal antibodies (mAbs) have been known to be useful in the identification of NDV due to their binding specificity, their homogeneity and their ability to be produced in unlimited quantities. It is, however, very difficult to obtain mAbs which are specific to NDV commercially. Therefore, this project is to develop mAbs against the local NDV strain AF2240. This velogenic-viscerotropic viral strain is a reference strain that has often been used for vaccine development. Hybridoma cells were created by fusing NDV-hyperimmunised Balblc splenocytes with Sp210-Ag14 (Sp2) myeloma cells using polyethylene glycol with the molecular weight of 1450 (PEG 1450). Positive clones were screened by ELISA. High titre producing clones were selected from a series of limiting dilutions. MAbs from stable hybridomas were further characterised by western blot analysis, haemagglutination-inhibition test (HI) and haemolysis-inhibition test (HLI). Eight hybridoma cell lines producing mAbs against the haemagglutininneuraminidase (HN) glycoprotein of NDV strain AF2240 were generated. Isotyping showed that mAbs 1B9, 2D6 and 9D7 were IgG1, mAbs 1D5, 5A10 and 5F10 were IgG2a and mAbs 2G3 and 5E10 were IgG3. Kappa (K) light chains were found in all mAbs. They can be divided into two groups: (1) mAbs lD5, 5A10 and 5E10 which recognised conformational and linearised epitopes and (2) mAbs 1B9, 2D6 and 9D7 which recognised only conformational epitopes. All mAbs showed positive results in the HI test but not HLI test conforming that they were specific to the HN protein and not the fusion (F) protein.